Implementation of Government Accounting Standards No. 07 and Management of Fixed Assets at the Regional Asset Financial Management Agency of Gowa Regency - Febrianti, St Maimuna; Idrawahyuni, Idrawahyuni; Wahyuni, Wahyuni (Contemporary Journal on Business and Accounting, 2025)
Purpose – This study aims to analyze the implementation of Government Accounting Standards No. 07 and Fixed Asset Management at the Regional Asset Financial Management Agency of Gowa Regency. Design/methodology/approach – This research uses a qualitative research method with a focus on the implementation of Government Accounting Standards and Fixed Asset Management. Findings – The results of this study indicate that the implementation of SAP No. 07 has been carried out in accordance with applicable provisions, but there are still technical obstacles, such as the lack of integration of the Electronic Regional Property (E-BMD) asset recording system with the Regional Government Information System (SIPD) regional financial system, as well as limited human resources in the implementation of asset inventory and assessment. Fixed asset management has been running according to regulations but its implementation in the field is still not optimal. Originality - This research lies in an in-depth study of the application of Government Accounting Standards by linking it to Fixed Asset Management. Keywords: GSAP No.07, Fixed Asset, SIPD, E-BMD, BPKAD